Long-term assessment of bladder and bowel dysfunction after radical hysterectomy - Brooks, Rebecca A.; Wright, Jason D.; Powell, Matthew A.; Rader, Janet S.; Gao, Feng; Mutch, David G.; Wall, L. Lewis (Gynecologic oncology, 2009)
To determine the long-term effects of radical hysterectomy on bladder and bowel function. Subjects included women who underwent radical hysterectomy for early stage cervical cancer between 1993 and 2003. Two contemporary controls who underwent extrafascial abdominal hysterectomy for benign disease were identified for each subject. Identified subjects and controls were surveyed. The Urogenital Distress Inventory (UDI) was used to assess symptoms of incontinence, and the Incontinence Impact Questionnaire (IIQ) was used to examine the impact of incontinence on quality of life. The Manchester Health Questionnaire and Fecal Incontinence Quality of Life Scale (FIQL) were used to assess anorectal symptoms. Surveys were returned by 66 of 209 (32%) subjects and 152 of 428 (36%) controls. Overall, 50% of subjects and 42% of controls reported mild incontinence symptoms; 34% of subjects and 35% of controls reported moderate–severe symptoms ( p = 0.72). Incontinence was associated with moderate–severe impairment in 18% of subjects and 14% of controls ( p = 0.74). Fecal incontinence symptoms were uncommon, not differing between subjects and controls. Urinary incontinence is relatively common after radical hysterectomy, but severe anorectal dysfunction is uncommon. Radical hysterectomy does not appear to be associated with more long-term bladder or anorectal dysfunction than simple hysterectomy.